Clinical characteristics and outcome of IgG4-related disease with hypocomplementemia: a prospective cohort study - Peng, Linyi; Lu, Hui; Zhou, Jiaxin; Zhang, Panpan; Li, Jieqiong; Liu, Zheng; Wu, Di; Zhang, Shangzhu; Yang, Yunjiao; Bai, Wei; Wang, Li; Fei, Yunyun; et al. (Arthritis research & therapy, 2021)
Immunoglobulin G4-related disease (IgG4-RD) is a newly recognized systemic, immune-mediated, and fibro-inflammatory disease. Hypocomplementemia was found in part of IgG4-RD patients especially in the setting of active disease. This study aimed to clarify the clinical features, treatment efficacy, and outcome in IgG4-RD patients with hypocomplementemia. 312 IgG4-RD patients were recruited in our prospective cohort conducted in Peking Union Medical College Hospital. Patients were divided into hypocomplementemia group and normal complement group according to serum C3 and C4 levels measured at baseline before treatment. Low serum C3 levels (< 0.73 g/L) and/or C4 levels (< 0.10 g/L) were defined as hypocomplementemia. Demographic data, clinical characteristics, laboratory parameters, treatment, and outcome of two groups were analyzed and compared. Hypocomplementemia was identified in 65 (20.8%) cases of untreated IgG4-RD patients at baseline. The average age of hypocomplementemia group was 55.85 ± 10.89 years, with male predominance (72.3%). Compared with normal complement group, patients with hypocomplementemia were likely to have more involved organs, higher IgG4-RD responder index (IgG4-RD RI), and higher laboratory parameters such as counts of eosinophils, inflammatory markers, immunoglobulin G (IgG), IgG1, IgG3, IgG4, and IgE. In addition, lymph nodes, lacrimal gland, submandibular gland, parotid gland, paranasal sinus, bile ducts, and prostate gland were more commonly affected (p < 0.05). Serum C3 and C4 showed a significant positively correlation with each other. Both C3 and C4 were negatively correlated with the number of involved organs, IgG, IgG3, IgG4, and IgG4-RD RI, as well as positively correlated with IgA and hypersensitive C reactive protein (hsCRP). 64 (98.5%) patients responded quickly to initial therapy at a 3-month follow-up. Fifteen (23.1%) patients relapsed during follow-up with mean recurrence time of 14.2 ± 13.8 months. Compared with normal complement group, there was no significant difference of relapse rate in two groups (P = 0.401). Clinical characteristics of IgG4-related disease with hypocomplementemia differ from normal complement group. Serum C3 and C4 at baseline before treatment could be biological markers for disease activity. IgG4-RD with hypocomplementemia responded well to treatment and had no significant difference of relapse rate in IgG4-RD with normal complement.